Physical-mechanical properties of palm kernel activated carbon-epoxy (PKAC-E) composite - Khudhair, Ahmed Qays (2016)
Palm kernel activated carbon-Epoxy (PKAC-E) composite possess good properties to function as a self-lubricated material in the dry sliding conditions. However, there are no previous studies have focused on the physical-mechanical properties of this composite. In this study, the effect of PKAC composition on the physical-mechanical properties of the composite was investigated. The polymer resin was reinforced with 65%, 70%, and 75% by weight of PKAC and compacted into a die at 70°C with 20-ton pressure for 15 minutes by using compaction technique. The specimens were prepared to conduct tensile, hardness,porosity, density, and water absorption tests. It was observed that the most interesting properties for PKAC-E composite have found in the hardness and density tests. The properties of PKAC-E composite 65-35% were better than other two composites 70-30% and 75-25% in terms of high hardness and low density, while the PKAC-E composite 70-30% was slightly better in terms of tensile strength properties. In addition, the PKAC-E composite 65-35 % has proved its superiority in terms of hardness and density properties with other synthetic-natural reinforced polymer composites. PKAC-E composite with the optimum properties has high hardness, lightweight, low-cost and can be very useful for further industrial applications and other machinery parts.